The Shift from Peso to SOEP: Strategic Communication and Visual Identity Strengthening in Arpose Project - Fatima Zahra Herdinawati; Dian Ajeng Kirana (Institut Seni Indonesia Yogyakarta, 2026)
Digital communication dynamics have driven a fundamental shift in media strategy, from the traditional PESO model toward the SOEP model (Shared, Owned, Earned, Paid Media), which is more adaptive to contemporary audience behavior. Through a case study of the interior design consultant Arpose Project, this research analyzes the role of repositioning media priorities as a communication strategy in building reputation and strengthening a competitive visual identity in the interior design industry. The analysis results show that, unlike the PESO model which places paid media as the primary reach trigger, Arpose Project effectively implements a SOEP strategy with Shared media through Instagram interactions and Owned media in the form of an official website as the primary foundation for building organic audience trust. In this ecosystem, Shared media functions as a space for dialogue and community participation, while Owned media acts as a platform for presenting portfolios and authentic, curated design philosophy narratives. The integration of these two elements gradually generates Earned media in the form of reputation and social proof, transforming Paid media into a tool for reinforcing the already established professional image. This research confirms that the SOEP strategy opens opportunities for interior design bureaus to anticipate audience hesitation toward promotional content through a transparent storytelling approach and consistent visual curation. The research method used is descriptive qualitative with a case study approach toward Arpose Project’s visual content, analyzed using the SOEP model shift framework.